Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Terhadap Kemampuan Komunikasi Matematis Peserrta Didik kelas VIII SMP N 21 Padang Tahun Ajaran 2018/2019 - PUTRI NADILA W (Jurnal Edukasi dan Penelitian Matematika, 2019)
The problen in this research is the low ability of mathematical communication that belongs to grade VIII students of SMP N 21 Padang. Teacher based learning is the cause of low learners mathematical skill. One of the many solutions that can improve the mathematical communication skill of the students is the implementation of Think Talk Write (TTW) cooperative learning modell. The reason of Think Talk Write (TTW) type learning modell is chosen to facilitate students to practice speaking both orally and writing. The purpose of this the study is to knowing and describe whether mathematical communication skills learned to use a Think Talk Write cooperative learning modell is better than the mathematical communication skills of the learners that to use direct learning modell in class VIII SMPN 21 Padang Year lesson 2018/2019. This research is conducted with the type of Quasy experiment research by using the modell design Randomized Control-Group  Only Design. The sample of this research is the student of VIII. Final tests and quizzers are the instruments used to collect data in this study. The result is the mathematical communication skill of learness who use a Think Talk Write modell of cooperative learning can improve. Communication skill of learness who use cooperative  learning modells of Think Talk Write are better than the communication skill of who learn to use a direct learning modell in grade VIII of SMP N 21 PadangKeywords – TTW learning modell, mathematical communication skill, direct learning